Implementasi Sosio Chemoentrepreneurship untuk Memproduksi Kebutuhan Rumah Tangga berbasis Sodium Lauril Sulfonat - Putri, Intan Cynara Valentina; Alti, Rahmi Mudia; Agustianti, Rifka; Wulandari, Ike Yuni; A, Yoana Nurul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This Community Service Program (PKM) aims to enhance the skills of housewives in producing hand soap, laundry detergent, and dishwashing liquid based on Sodium Lauryl Sulfonate (SLS). The methods used include socialization, training, mentoring, monitoring, and evaluation, involving 20 participants divided into three groups. Evaluation results showed a significant improvement in participants' understanding, with an average post-test score increase of 43% compared to the pre-test. 90% of participants felt more confident, 85% were interested in entrepreneurship, and 75% recognized its economic benefits. However, limitations included a short training duration and limited equipment. Future recommendations include extended mentoring and marketing training to help participants develop sustainable businesses.